2021
DOI: 10.3389/fmolb.2021.775562
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Radiosensitivity Gene Signature and PD-L1 Status Predicts Clinical Outcome of Patients With Locally Advanced Head and Neck Squamous Cell Carcinoma: A Study Based on The Cancer Genome Atlas Dataset

Abstract: Aim: The aim of our study was to investigate the potential predictive value of the combination of radiosensitivity gene signature and PD-L1 expression for the prognosis of locally advanced head and neck squamous cell carcinoma (HNSCC).Methods: The cohort was selected from The Cancer Genome Atlas (TCGA) and classified into the radiosensitive (RS) group and radioresistant (RR) group by a radiosensitivity-related gene signature. The cohort was also grouped as PD-L1-high or PD-L1-low based on PD-L1 mRNA expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
(64 reference statements)
1
5
0
Order By: Relevance
“…Additionally, using TSA in conjunction with immune treatment and radiation therapy seems to enhance the prognosis for head and neck cancer, according to the cancer genome dataset. These pre-clinical study findings support the significance of TSA to assist in the tumor removal in cancer treatment, despite the lack of TSA use in the clinical experiments yet [ 44 ].…”
Section: The Renaissance Of Natural Compounds In Cancer Therapy: An U...supporting
confidence: 57%
“…Additionally, using TSA in conjunction with immune treatment and radiation therapy seems to enhance the prognosis for head and neck cancer, according to the cancer genome dataset. These pre-clinical study findings support the significance of TSA to assist in the tumor removal in cancer treatment, despite the lack of TSA use in the clinical experiments yet [ 44 ].…”
Section: The Renaissance Of Natural Compounds In Cancer Therapy: An U...supporting
confidence: 57%
“…GEO datasets have been increasingly used as advanced and convenient tools for the quick screening of candidate genes related to specific biological processes including radioresistance in cancer [ 29 31 ]. In this study, by analyzing GSE31863 and GSE101920 datasets and querying TCGA-BRCA database, we obtained UBE3C as an upregulated gene in BRCA tissue samples following radioresistance and its elevation was linked to poor radioresponse.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on radiosensitivity in head and neck cancer have identified some related genes. Some are based on the gene expression levels of cell lines [ 50 , 51 ], and some are based on gene expression levels in tumors and patient survival data [ 52 , 53 ]. Foy et al analyzed the data from the public database by data mining.…”
Section: Discussionmentioning
confidence: 99%